KSHV ORF59 and PAN RNA Recruit Histone Demethylases to the Viral Chromatin during Lytic Reactivation - Hiura, Kayla (Viruses, 2020)
Kaposi’s sarcoma-associated herpesvirus (KSHV) causes multiple malignancies in immunocompromised individuals. KSHV primarily establishes a lifelong latency in infected humans during which only a subset of viral genes is expressed while most of the viral genome remains transcriptionally silent with condensed chromatin. However, during the lytic phase, the viral genome undergoes dramatic changes in chromatin landscape leading to a transcriptionally active state with the expression of most of the viral genes and production of progeny virions. Multiple cellular and viral factors influence the epigenetic gene regulation and transitioning of virus from latency to the lytic state. We have earlier shown that KSHV ORF59, viral processivity factor, binds to a protein arginine methyl transferase 5 (PRMT5) to alter the histone arginine methylation during reactivation. Additionally, ORF59 has been shown to interact with most abundantly expressed KSHV long noncoding polyadenylated nuclear RNA (PAN RNA), which associates with the viral epigenome during reactivation. Interestingly, PAN RNA interacts with UTX and JMJD3, cellular H3K27me3 demethylases, and removes the repressive marks on the chromatin. In this study, we report that the recruitment of histone demethylases to the viral chromatin is facilitated by the expression of ORF59 protein and PAN RNA. Using biochemical and localization assays including co-immunoprecipitation and immunofluorescence, we demonstate ORF59 localizes with UTX and JMJD3. Our results confirm that PAN RNA enhances the interaction of ORF59 with the chromatin modifying enzymes UTX and JMJD3.